2014
DOI: 10.1155/2014/105709
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Duration of Urine Leakage following Percutaneous Nephrolithotomy

Abstract: Purpose. The duration of urine leakage following the removal of the nephrostomy tube after percutaneous nephrolithotomy (PCNL) shows significant variations depending on the techniques used. We aimed to assess the factors likely to influence the duration of urine leakage. Material and Methods. In total, 103 patients who underwent PCNL were reviewed retrospectively. DUL was evaluated regarding patient characteristics, thickness of the access line, presence of hydronephrosis, and residual stones. Results. DUL was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
3
7
1
Order By: Relevance
“…This may cause PUL due to delayed healing resulting from decreased blood supply to this area and the loss of the compressive properties of the thin parenchyma. Uyeturk et al reported that the renal parenchymal thickness in the access line showed a more significant correlation with the duration of urinary leakage com-pared to the degree of hydronephrosis (20), which was also supported by Ansari et al (18). In our study, we showed that renal parenchymal thickness in the access line was a factor predicting PUL.…”
Section: Discussionsupporting
confidence: 87%
“…This may cause PUL due to delayed healing resulting from decreased blood supply to this area and the loss of the compressive properties of the thin parenchyma. Uyeturk et al reported that the renal parenchymal thickness in the access line showed a more significant correlation with the duration of urinary leakage com-pared to the degree of hydronephrosis (20), which was also supported by Ansari et al (18). In our study, we showed that renal parenchymal thickness in the access line was a factor predicting PUL.…”
Section: Discussionsupporting
confidence: 87%
“…[ 12 ] reported that stone burden prolongs the duration of hospital stay due to prolonged urinary leakage while Uyeturk et al . [ 13 ] demonstrated opposite results. We do not think that stone burden influences the post-PCNL prolonged urinary leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Uyeturk et al . [ 13 ] reported that renal parenchymal thickness in access line is more significantly correlated with duration of urinary leakage than grade of hydronephrosis. The present study also confirmed that renal parenchymal thickness in access line inversely correlated with prolong urinary leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The association between renal PT and UL has been investigated in some studies. Uyetürk et al [16] found 17.2 mm optimum cut-off value of PT for hospitalization ≤ 12 h with 90.2% sensitivity and 69.4% specificity. Ansari et al [4] determined 17 mm cut-off value of PT hospitalization of patients due to prolonged urinary leakage with 95.2 sensitivity and 60.2% specificity.…”
Section: Discussionmentioning
confidence: 99%